Asymptomatic lung nodules in dental professionals: A diagnostic challenge. (2022) - Godallage, Anuradha N.; Kolekar, Shailesh; Olsen, Karen Ege; Bonnesen, Barbara; Petersen, Jesper Koefod; Clementsen, Paul F.; Bodtger, Uffe; Sivapalan, Pradeesh
Abstract: Dental care workers are frequently exposed to various types of volatile organic and inorganic compounds. In addition to biological materials, these compounds include silica, heavy metals, and acrylic plastics. Such exposures may cause respiratory symptoms, but the nonspecific nature of these symptoms often means that the etiology is difficult to discern. The disease severity depends on the particle size and type of the inhaled compounds, as well as the duration and intensity of exposure, which varies markedly among dental workers. Here, we present two unique cases with the same occupational exposure. Both patients showed radiological changes in the lungs that were suspicious for lung cancer. The first patient did not undergo a biopsy due to cardiac comorbidities and risk of bleeding, and the diagnosis was based on thoracic computer tomography (CT) which confirmed multiple, bilateral, solid, smooth, partly calcified lung nodules, normal positron emission tomography (PET)-CT and the relevant occupational exposure. In the second case, a CT-guided biopsy and thoracoscopic resection was done with histopathological findings consistent with granuloma. The multi-disciplinary team decision of both cases was consistent with occupational exposure related lunge disease. This is the first case study report whereby same occupational exposure related health condition is compared with two different approaches. Respiratory clinicians should be aware of this potential diagnosis, especially for asymptomatic patients with relevant exposures. Careful attention to the occupational history may help to prevent unnecessary, invasive diagnostic procedures or surgeries.